PIALA DUNIA DI QATAR: PERSPEKTIF DAKWAH ISLAM - Muhith Muhammad Ishaq (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This paper analyzes the meaning of da'wah in the 2022 World Cup competition in Qatar. This qualitative research uses literature and interprets textually. The data used are written websites, journals, books, Al-Qur'an, Hadith and other library sources. This paper concludes that football at the 2022 world cup in Qatar does not only take the form of the popularity of football as a global people's game, more than that, this event is interesting because it was the first time it was held in a Middle Eastern Muslim country which is synonymous with Islamic teachings and civilization in when the eyes of the world have looked at Islam and Muslims in recent decades as marginal, backward entities, and not a few who are attached to violence, terrorism and other corners, and Qatar appears as a window for Muslims displaying an image of Islam that is relevant to the spirit of football. a ball that adheres to the values of sportsmanship, fair play, universality, humanism and human values that do not discriminate against race, skin color, nation and religion, displays a progressive Islam, respects and welcomes guests with honor, entrusts a deep message to the whole world about Islam peaceful